Learning of Craft and Entrepreneurship Towards Student’s Entrepreneurship Interest Referred from Planned Behavior (International Journal of Active Learning, 2019)
The purpose of this research is to see the relation between learning of craft and entrepreneurship in theory of planned behavior (Ajzen, 1991) and further influence entrepreneur interest. The population of this research is on students of marketing program of SMK Negeri Kabupaten Boyolali with Smart PLS-3.0 analysis tool. Through the sampling formula Issac and Michael obtained as many as 175 student samples. Sampling is by proportionate stratified random sampling technique. The results of the analysis show that: learning of craft and entrepreneurship have positive effect on entrepreneurship interest through mediation by attitude toward behavior (ATB), subjective norm (SN), and perceived behavior control (PBC). The research is well used in the development of economic learning innovation especially on the subjects of craft and entrepreneurship